Primate archaeology 3.0 - Pascual-Garrido, A; Carvalho, S; Almeida-Warren, K (Wiley, 2023)
The new field of primate archaeology investigates the technological behavior and material record of nonhuman primates, providing valuable comparative data on our understanding of human technological evolution. Yet, paralleling hominin archaeology, the field is largely biased toward the analysis of lithic artifacts. While valuable comparative data have been gained through an examination of extant nonhuman primate tool use and its archaeological record, focusing on this one single aspect provides limited insights. It is therefore necessary to explore to what extent other non-technological activities, such as non-tool aided feeding, traveling, social behaviors or ritual displays, leave traces that could be detected in the archaeological record. Here we propose four new areas of investigation which we believe have been largely overlooked by primate archaeology and that are crucial to uncovering the full archaeological potential of the primate behavioral repertoire, including that of our own: (1) Plant technology; (2) Archaeology beyond technology; (3) Landscape archaeology; and (4) Primate cultural heritage. We discuss each theme in the context of the latest developments and challenges, as well as propose future directions. Developing a more “inclusive” primate archaeology will not only benefit the study of primate evolution in its own right but will aid conservation efforts by increasing our understanding of changes in primate-environment interactions over time.